2005
DOI: 10.1016/j.nima.2005.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the limiting timing resolution for large volume CZT detectors with waveform analysis

Abstract: This paper presents a study for exploring the limiting timing resolution that can be achieved with a large volume 3-D position sensitive CZT detector. The interaction timing information was obtained by fitting the measured cathode waveforms to pre-defined waveform models. We compared the results from using several different waveform models. Timing resolutions, of ~9.5 ns for 511 keV full-energy events and ~11.6 ns for all detected events with energy deposition above 250 keV, were achieved with a detailed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…The time taken by electrons to drift through the entire detector thickness can be accurately determined using pulse waveform analysis [10], [11]. A typical cathode pulse waveform is shown in Fig.…”
Section: B Electron Mobility and Lifetime Measurementsmentioning
confidence: 99%
“…The time taken by electrons to drift through the entire detector thickness can be accurately determined using pulse waveform analysis [10], [11]. A typical cathode pulse waveform is shown in Fig.…”
Section: B Electron Mobility and Lifetime Measurementsmentioning
confidence: 99%
“…Alternatively, sophisticated processing of events that involve multiple anode pixels may allow one to utilize all events detected by small anode pixel CdZnTe detectors for imaging purposes. Although the characteristics of the CdZnTe detectors have been widely investigated over the last decade (Bolotnikov et al 1999, He et al 2000, Meng and He 2005), little has been reported about CdZnTe as a PET detector (Vaska et al 2007, Gu et al 2011) and we did not find any publication about a CdZnTe PET detector with anode pixel size less than 0.5 mm.…”
Section: Introductionmentioning
confidence: 76%
“…The result is that CZT detectors have more timing jitter and time walk, which degrades the coincidence time resolution. Meng and He (2005) have shown that time resolution of ~10 ns may be achieved if the full waveform from each event were digitized for analysis. However, our RENA-3 based data acquisition system does not enable this as it samples only the pulse peak value, and uses a leading edge discriminator for time pick-off.…”
Section: Discussionmentioning
confidence: 99%